Efficacy of an Interdisciplinary Intensive Outpatient Program in Treating Combat-Related Traumatic Brain Injury and Psychological Health Conditions - DeGraba, Thomas J.; Williams, Kathy; Koffman, Robert; Bell, Jennifer L.; Pettit, Wendy; Kelly, James P.; Dittmer, Travis A.; Nussbaum, George; Grammer, Geoffrey; Bleiberg, Joseph; French, Louis M; Pickett, Treven C. (Frontiers in Neurology, 2021)
Background: Since 2000, over 413,000 service members (SM) experienced at least one traumatic brain injury (TBI) and 40% of those with in-theater TBIs later screened positive for comorbid psychological health (PH) conditions including post-traumatic stress disorder (PTSD), depression, and anxiety. Many SMs with these persistent symptoms fail to achieve a recovery that results in a desirable quality of life or return to full duty. Limited information, though, exists to guide treatment for SMs with a history of mild TBI (mTBI) and comorbid PH conditions. This report describes the methods and outcomes of an interdisciplinary intensive outpatient program (IOP) in the treatment of SMs with combat-related TBI and PH comorbidities. The IOP combines conventional rehabilitation therapies with integrative medicine techniques with the goal of reducing morbidity in multiple neurological and behavioral health domains and enhancing military readiness. Methods: SMs (n = 1,456) with residual symptoms from mTBI and comorbid PH conditions were treated in a 4-week IOP at the National Intrepid Center of Excellence (NICoE) at Walter Reed National Military Medical Center (WRNMMC). The IOP uses an interdisciplinary, holistic, and patient-centric rehabilitative care model. Interdisciplinary teams provide a diagnostic workup of neurological, psychiatric, and existential injuries and from these assessments individualized care plans are developed. Treatment response was assessed using the Neurobehavioral Symptom Inventory (NSI), PTSD Checklist-Military Version (PCL-M), Satisfaction with Life Scale (SWLS), Patient Health Questionnaire-9 (PHQ-9), Generalized Anxiety Disorder-7 (GAD-7), Epworth Sleepiness Scale (ESS), and Headache Impact Test-6 (HIT-6) and administered at admission, discharge, and 1, 3, and 6 months post-discharge. Findings: Following treatment in the IOP, symptomatic patients had statistically significant and clinically meaningful improvements across all outcome measures. The largest effect size was seen with the GAD-7 (r = 0.59) followed by the PHQ-8 (r = 0.56), NSI (r = 0.55), PCL-M (r = 0.52), ESS (r = 0.50), SWLS (r = 0.49), and HIT-6 (r = 0.42). In cross sectional follow ups, the significant improvements were sustained at 1, 3, and 6-month post-discharge. Interpretation: This report demonstrates that an interdisciplinary IOP achieves significant and sustainable symptom recovery in SMs with combat-related mTBI and comorbid PH conditions.